Comparative Adsorption Study of Functionalized Magnetite and Maghemite Nanoparticles Coated with CTAB Surfactant for Efficient Chromium Removal from Wastewater - Mohamed Naous; Ahmed Halfadji (Journal of Water and Environmental Nanotechnology)
In this study, maghemite and magnetite nanoparticles were functionalized with cetyl trimethyl ammonium bromide(CTAB) surfactants, in order to obtain effective chromium removal from wastewater. X-ray diffractometry (XRD), transmission electron microscopy (TEM), and Fourier-transform infrared spectrophotometry (FTIR) were used to characterize the functionalized nanoparticles. Various parameters, including pH, initial chromium concentration, added salt, and adsorbent dose, were evaluated in batch experiments to evaluate chromium removal efficiency. Adsorbent dose and chromium ions show a synergistic relationship with pH and the chemical and electrostatic interactions between cationic surfactant and negatively charged Cr(VI) ions. In both types of functionalized nanoparticles, Cr(VI) was efficiently removed at low pH values with CTAB@MNPs, but the pH increased negatively impacted the removal process. Additionally, Fe3O4@CTAB mainly adsorbs chromium chemically, reducing Cr(VI) to Cr(III), with less impact from competitive ions compared with γ-Fe2O3@CTAB.At pH = 2, adsorbent dose = 5 g/L, and initial chromium concentration = 1 mg/L, maghemite@CTAB achieved a high chromium removal efficiency of 95%. In contrast, magnetite@CTAB achieved a chromium removal efficiency of 95.77% in 7 minutes and 30 seconds at pH = 4, adsorbent dose = 12 g/L, and initial chromium concentration = 98 mg/L. Notably, magnetite outperformed maghemite by a factor of 100 in chromium elimination, which can be attributed to the presence of two adsorption mechanisms, chemical and physisorption, in magnetite nanoparticles, whereas maghemite only had physisorption.